2001
DOI: 10.1093/jnci/93.22.1739
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanism for the Effects of Dexamethasone on Growth of Androgen-Independent Prostate Cancer

Abstract: Dexamethasone inhibited the growth of GR-positive cancers, possibly through the disruption of the NF-kappaB-IL-6 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
115
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 31 publications
8
115
1
Order By: Relevance
“…Reporter gene assay showed that the promoter fragment containing this GRE motif was activated by androgen treatment at AR-dependent manner in LNCaP cells that are null of glucocorticoid receptor (GR). 35 Because the AR and the GR are closely related members in the steroid hormone receptor family, 22 it is plausible that this GRE (termed as ARE-1) motif is involved in androgen-induced SGK-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Reporter gene assay showed that the promoter fragment containing this GRE motif was activated by androgen treatment at AR-dependent manner in LNCaP cells that are null of glucocorticoid receptor (GR). 35 Because the AR and the GR are closely related members in the steroid hormone receptor family, 22 it is plausible that this GRE (termed as ARE-1) motif is involved in androgen-induced SGK-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, high serum levels of IL-6 in PAC patients have been linked to disease progression, hormone-independence and chemotherapy resistance (Nakashima et al, 2000;Sanchez-Perez et al, 2002;Michalaki et al, 2004). Also, dexamethasone, a glucocorticoid used commonly for prostate cancer treatment, disrupts the NF-kB-IL-6 pathway and this is thought to mediate the antitumour effect (Nishimura et al, 2001). Finally, recent evidence in a phase I clinical trial has suggested that the proteasome inhibitor bortezomib has activity against human prostate cancer and reduces the expression of serum IL-6 and PSA levels in some patients (Papandreou and Logothetis, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we evaluated the effect of dexamethasone (DEX) on the luciferase activities of LF4 and LF7 in the cells co-transfected with a GR expression vector. This is because DEX is known to downregulate GR expression in LANCaP cells (19,20). First, we examined the luciferase activities of LF4 in the LNCaP cells, which was co-transfected with either hGR· or hGRß, with or without dexamethasone (DEX) treatment.…”
Section: Downregulation Of 15-lox-2 Promoter Activity By the Glucocormentioning
confidence: 99%